A 12-week combination of clarithromycin and prednisone compared to a 24-week prednisone alone treatment in cryptogenic and radiation-induced organizing pneumonia - Petitpierre, Nicolas; Cottin, Vincent; Marchand-Adam, Sylvain; Hirschi, Sandrine; Rigaud, Dominique; Court-Fortune, Isabelle; Jouneau, Stéphane; Israël-Biet, Dominique; Molard, Anita; Cordier, Jean-François; Lazor, Romain (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Background: Some data suggest that anti-inflammatory macrolides may be effective to treat organizing pneumonia (OP) and prevent relapses, but no formal comparison with prednisone alone is available. To explore this issue, we retrospectively compared the efficacy of a 12-week combined regimen of clarithromycin and prednisone with a 24-week prednisone alone regimen in OP. Methods: A standard 12-week regimen of combined clarithromycin and prednisone was designed for the treatment of cryptogenic or radiation-induced OP, aiming at reducing the cumulated prednisone dose and the relapse rate. Its use was left to the discretion of the treating physicians, members of the Groupe d’Etudes et de Recherche sur les Maladies Orphelines Pulmonaires. Data were compared to a historical control group treated with a standard 24-week prednisone alone regimen. Results: 16 patients were treated with combined therapy and 21 with prednisone alone. Complete radiological remission was achieved in 63% of the combined therapy group and 81% of the prednisone alone group (p=0.38). Symptomatic relapses occurred in 81% of the combined therapy group, and 52% of the prednisone alone group (p=0.14). No side effect of clarithromycin was reported. Conclusions: In patients with cryptogenic or radiation-induced OP, a 12-week regimen of clarithromycin and prednisone showed no benefit on remission rate and relapse rate as compared to a 24-week prednisone only regimen.